2007
DOI: 10.1113/jphysiol.2007.132415
|View full text |Cite
|
Sign up to set email alerts
|

The effects of repeated exposure to hypercapnia on arousal and cardiorespiratory responses during sleep in lambs

Abstract: Arousal and cardio-respiratory responses to respiratory stimuli during sleep are important protective mechanisms that rapidly become depressed in the active sleep state when episodes of hypoxia or asphyxia are repeated: whether responses to repeated hypercapnia are similarly depressed is not known. This study aimed to determine if arousal and cardio-respiratory responses also become depressed with repeated episodes of hypercapnia during sleep and whether responses differ in active sleep and quiet sleep. Eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…These results are somewhat different from those of Buchanan and Richerson, who showed that WT mice exhibit robust arousal from REM sleep in response hypercapnia while Lmx1bϪ/Ϫ mice essentially fail to arouse in response to the challenge (6). Others have found that the arousal of young animals in response to hypercapnia is delayed in AS compared with QS (15,20). It appears that in early postnatal life groups of neurons that normally terminate AS are, unlike respiratory neurons that promote the hypercapnic ventilatory response, insensitive to inputs originating from central CO 2 chemoreceptive sites.…”
Section: Arousal In Response To Hypercapnia Is Delayed By Central 5-hmentioning
confidence: 60%
“…These results are somewhat different from those of Buchanan and Richerson, who showed that WT mice exhibit robust arousal from REM sleep in response hypercapnia while Lmx1bϪ/Ϫ mice essentially fail to arouse in response to the challenge (6). Others have found that the arousal of young animals in response to hypercapnia is delayed in AS compared with QS (15,20). It appears that in early postnatal life groups of neurons that normally terminate AS are, unlike respiratory neurons that promote the hypercapnic ventilatory response, insensitive to inputs originating from central CO 2 chemoreceptive sites.…”
Section: Arousal In Response To Hypercapnia Is Delayed By Central 5-hmentioning
confidence: 60%
“…Muscle sympathetic nerve activity is recruited during obstructive events in OSA patients 35 ; however studies in lambs indicate that the hypertension caused by hypercapnia is reduced during REM-like sleep states 39 . Consistent with the latter, the pressor effect of photostimulation was attenuated during REMS.…”
Section: Resultsmentioning
confidence: 99%
“…In tracheotomized lambs the probability of arousal in response to hypercapnia was greater during QS compared to AS (Fewell et al , 1989b; Johnston et al , 2007). Another study in lambs showed that arousal latencies during hyperoxic hypercapnia were significantly longer in AS (58 ± 17 sec) compared to QS (21 ± 10 sec) (Fewell & Baker, 1989).…”
Section: Arousal In Response To Hypercapniamentioning
confidence: 92%